2022
DOI: 10.1007/s12031-022-02039-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Brain-Derived Neurotrophic Factor (BDNF) in COVID-19 Patients and its Association with the COVID-19 Manifestations

Abstract: COVID-19 is a systematic disease that frequently implies neurological and non-neurological manifestations, predominantly by inducing hypoxia. Brain-derived neurotrophic factor (BDNF) is a key factor in regulating functions of nervous and respiratory systems and has been strongly related to hypoxia. Therefore, this study planned to investigate BDNF association with the COVID-19 manifestations especially neurological impairments and the infection-induced hypoxia. We enrolled sixty-four COVID-19 patients and twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…In a study involving 64 COVID-19 (+) patients there was a significant reduction in BDNF level among patients as compared to the control group. This difference was greatest in a group with the neurological manifestation of COVID-19, and smaller in patients with only fever and dyspnea [ 154 ]. A decrease in BDNF level in COVID-19 patients depending on their condition has also been observed in other studies and it was negatively correlated with the severity of the patients’ condition, and its normalization followed the improvement of the clinical condition [ 155 , 156 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving 64 COVID-19 (+) patients there was a significant reduction in BDNF level among patients as compared to the control group. This difference was greatest in a group with the neurological manifestation of COVID-19, and smaller in patients with only fever and dyspnea [ 154 ]. A decrease in BDNF level in COVID-19 patients depending on their condition has also been observed in other studies and it was negatively correlated with the severity of the patients’ condition, and its normalization followed the improvement of the clinical condition [ 155 , 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies seem to confirm that COVID-19 infection causes a decrease in BDNF levels [ 154 , 155 , 156 ]. These results, however, are not consistent in all cases and there are studies that do not show a decrease in BDNF, or even its increase among patients who developed “long-COVID” [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…Altered expression of genes include CX3CR1 [666], S100A12 [667], CSF2 [668], MPO (myeloperoxidase) [669], CD5L [670], F11 [671], S100A8 [672], PGLYRP1 [673], VEGFD (vascular endothelial growth factor D) [674], CXCL11 [373], BPI (bactericidal permeability increasing protein) [675], CXCL10 [676], S100A9 [677], CXCR1 [678], CXCR2 [679], ABCA3 [680], CD36 [681], SHH (sonic hedgehog signaling molecule) [682], TLR3 [683], CLEC4D [684], CCR2 [685], NEK7 [686], TLR7 [687], CCRL2 [688] and CAV1 [689] accelerates pneumonia progression. CX3CR1 [666], CD177 [690], PF4 [691], FFAR2 [692], MPO (myeloperoxidase) [693], F11 [694], S100A8 [695], VEGFD (vascular endothelial growth factor D) [674], IL1A [696], BPI (bactericidal permeability increasing protein) [697], AQP4 [698], BDNF (brain derived neurotrophic factor) [699], CXCL10 [700], RNASE2 [701], FCGR3B [702], S100A9 [703], IL1B [704], CXCR2 [705], GPIHBP1 [294], CD36 [706], TRIB3 [707], PCSK9 [708], FGF2 [709], FASN (fatty acid synthase) [710], PNPLA3 [711], HSPA6 [712], VIP (vasoactive intestinal peptide) [713], TLR3 [683], ADRB1 [328], SPOCK2 [714], TLR8 [715], CCR2 [716], IFIT3 [717], NEK7 [718], TLR7 [687], EFNB2 [719], CAV1 [720], CR1 [721] and AQP5 [722] plays essential roles in viral respiratory diseases. Previous study confirmed that CX3CR1 [723], S100A12 [724], CD177 [725], PF4 [726], MPO (myeloperoxidase) [727], CD5L [728], F11 […”
Section: Discussionmentioning
confidence: 99%
“…Overall, research in this area is advancing. For instance, some studies have found an association between low neurotrophic factors and COVID-19-related neuropsychiatric complications [ 99 ]; thus, neurotrophic drugs such as cerebrolysin may serve as a potential therapeutic approach to improve neuropsychiatric manifestations of COVID-19 [ 100 ]. Clearly, more research studies and clinical trials are needed in this regard.…”
Section: Discussionmentioning
confidence: 99%